LEGAL IMPACT ON WAQF FOR PROPERTY DEVELOPMENT AND COMMERCIALISATION: COURT JUDGEMENTS ANALYSIS - Mohd Zakhiri Bin Md Nor; Alias Azahar; Ani Munirah Mohamad; Al Hanisham Mohd Khalid (Journal of Islamic, Social, Economics and Development, 2019)
There are 24000 hectares of waqf land not be fully developed in 2016 based onWaqf Foundation of Malaysia report. These waqf lands need to be developed for propertydevelopment and commercialisation. However, there are many issues remained unsettledinter alia the interface between waqf and wasiat, the validity of waqf, the category of waqfland in particular leasehold and freehold of waqf land as well as the jurisdiction of thecourt to hear the case of waqf.It seems that all these issues may hamper the developmentand commercialisation of waqf land. Therefore, this paper shall analyse the administrationof waqf land in Penang. This paper also shall examine the legal impact on waqf for propertydevelopment and commercialisation through case analysis and court judgments. Themethodology used in this paper is qualitative and content analysis method. This paperprovides some suggestions and recommendations for better governance of waqf landparticularly for property development and commercialisation